River water chemistry, channel morphometrics, and river incision data for the Rio Bermejo, Argentina - Marisa N Repasch; Joel S Scheingross; Kristen L Cook; Dirk Sachse; Sophia Dosch; Oscar Orfeo (PANGAEA, 2023)
This dataset was generated to study the effects of lithospheric flexure on river geomorphology and river water chemistry of the Rio Bermejo fluvial system in the east Andean foreland basin of northern Argentina. Tectonics exerts a strong control over the morphology of Earth extquotesingles surface that is apparent in active mountain belts. In lowland areas, subtle processes like lithospheric flexure and isostatic rebound can impact Earth surface dynamics, hydrologic connectivity, and topography, suggesting that geomorphic and hydrologic analyses can shed light on underlying lithospheric properties. The Rio Bermejo is an outstanding field laboratory to study these feedbacks because it has a long reach that traverses the foreland basin without any tributaries. To examine the hydrologic effects, we sampled river water from the Rio Bermejo at several stations along the lowland flow path and measured dissolved solute concentrations (major cations and anions) and stable isotope composition (d2H and d18O). Additionally, we collected a timeseries of water samples for stable isotope measurements, where water samples were collected every week from March 2016 to February 2018 at the Lavalle bridge on the lower Rio Bermejo (Time series of water samples and stable water isotope measurements collected at Puente Lavalle (-25.6513, -60.1277).